Asas-Asas Utama dalam Perjanjian: Perspektif Hukum Perdata Indonesia - Santy Fitnawati WN; Meisha Amelia Hayatinnufus; Nilam Cahya Listyani; Riki Gana Suyatna (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
A contract is an important legal tool in society, whether in business, family, or personal relationships. In civil law, a contract not only regulates the rights and obligations of the parties involved, but also must adhere to several principles that underpin its validity and execution. This article aims to analyze the key principles in contracts under Indonesian civil law, such as the principle of freedom of contract, the principle of consensualism, the principle of good faith, the principle of pacta sunt servanda, the principle of balance, and the principle of compliance with the law. This study demonstrates that these principles not only serve as guidelines in drafting contracts, but also provide legal certainty for the parties involved. In practice, the application of these principles is crucial to avoid injustice and abuse during the contracting process.